Social Media Marketing Strategies to Increase Student Enrollment in Online Qur’an Learning Services - Dimas Triananda; Siskandar Siskandar; Akhmad Shunhaji (Indonesian Journal Education, 2025)
This study aims to analyze the marketing strategies of Qur’an learning services through social media in an effort to increase the number of students at the Qur’an30Challenge institution. The background of this research is based on the high rate of Qur’anic illiteracy in Indonesia and the growing competition among online learning institutions that utilize social media as a promotional tool. The research method employed is descriptive qualitative, with data collection techniques including in-depth interviews, observation, and documentation involving institutional leaders and students. Data analysis was conducted descriptively through a triangulation approach to ensure data validity and reliability. The results of the study indicate that the marketing strategies implemented by Qur’an30Challenge generally meet digital marketing standards and have had a positive impact on increasing student enrollment. However, several aspects still require development, such as market segmentation expansion, pricing adjustments, brand communication consistency, long-term evaluation, promotional budget optimization, the use of influencers, as well as content innovation and service quality improvement. This study underscores the importance of adapting marketing strategies to the dynamics of social media and consumer behavior as a key factor for the success of online learning institutions.